Quantity and Quality of Ethanol Produced by Utlization of Sorghum bicolor Grains - Sulieman, Abdel Moneim E.; Abo Shora, Waleed A. H.; Elkhalifa, ² Elamin A.; A.Gasmalla, Mohammed A. (Gezira Journal of Engineering and Applied Sciences, 2018)
The present study was conducted to investigate the production of ethanol from sorghum grains ( Feterita ) and evaluation of its quality. Proximate chemical composition in terms of protein, crude fiber, moisture, ash, oil and carbohydrate contents were determined in sorghum grains and malted grains flours. The results indicated that sorghum grains flour contained 12.7% protein, 1.6% crude fiber, 5.3% moisture, 1.8% ash, 2.7% oil and 76.1% carbohydrates. On the other hand, malted  grains flour contained 13.1% protein, 1.7% crude fiber, 5.5% moisture, 2% ash, 2.8% oil and 74.9% carbohydrates. Malt and pure enzymes (α-amylase and amyloglucosidase) were used to convert the starch to fermentable sugars. The yield of ethanol in fermented mash was 13% in the malt and 16% as a result of using pure enzymes. The ethanol volume produced from sorghum grains by malt and pure enzymes was 33 and 35 ml, respectively. The purity, density and viscosity of resulted ethanol were 95%, 0.83 gm / ml and 0.99 cip, respectively.